Proposal for quality control of ecological soap developed from recycled vegetable oil - Tescarollo, Iara Lúcia; Thomson Junior, José Pedro; Amâncio, Marilene de Souza; Alves, Tatiana Finotti Teixeira (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The frying oil flowing into the environment hascaused significant environmental impacts. Due to this fact , several proposals have emerged in order to reuse this oil and minimize its pollution action. One way to use this frying oil is its saponification to the household soap production in artisanal scale , the subject of great interest for some communities, institutions and organizations that have not only taken this pollutant of the environment, as has also allowed the alternative income generation. This study aimed to evaluate the quality of different batches of soap produced with residual oil , using tests to evaluate the sensory characteristics , middleweight , primary stability, foaming, crack formation, weight loss and softening and weight loss during storage. Variations of these properties assessed were found, which may be due to the diversity of origin, type, conditions of transport, storage and even the degree of rancidity of the oil used in the production of soaps. This study also had the intention to provide data that can contribute to viable alternatives reuse of this type of environmental contaminant.